Accidents at work by excessive efforts / inappropriate movements in nurses - Martins, Matilde (2016)
Nurses continuously develop various activities that expose them to excessive force and inappropriate movements. Characterize the accidents reported by overexertion and inappropriate movements in Portuguese nurses during 2009 and 2010. Retrospective cross-sectional study, covering the period from January 1, 2009 to December 31, 2010. Were defined as inclusion criteria, be nurse and having notified by excessive straining and improper motion accident. The information was obtained by reference to the computer record of accidents at work General Administration of Health Services, relating to 672 nurses. There were 672 notifications of accidents by overexertion/ inappropriate moves in Portuguese nurses. The higher prevalence of these accidents was in nurses with over 10 years of service 277 (41.2%), 565 were female (42.6%) in the age group 25-29 (29.9%) and practice time for 555 shifts (82.6%). At admission there were 387 (57.3%) within 3 hours of work 330 (49.1%) and the third day after weekly rest 216 (32.1%). The Mobilization of patients was the most frequent cause of this accident 430 (64.0%). The main effects were the sprains and strains 321 (47.8%), mainly the trunk reached 367 (54.7%) and absenteeism caused 373 (55.5%). On average 17.7 days missed a total of 12.054 days. There was a high prevalence of accidents during the mobilization of prayer on patients so importante to invest in the implementation of mechanical equipment for the mobilization and transport of patients.